2015
DOI: 10.5539/gjhs.v8n1p14
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits and Identity Styles in Methamphetamine-Dependent Women: A Comparative Study

Abstract: Background:Studies over the past two decades have shown that various personality traits of substance-dependent men measure differently than compared to normal individuals. However fewer studies have addressed the role of identity as an influential factor in the onset and continuation of drug dependency.Methods:The objective of this study was to compare the Big Five personality factors and identity styles in methamphetamine dependent women and non-user group. Forty eight methamphetamine dependent women under tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
(39 reference statements)
0
4
1
2
Order By: Relevance
“…Interestingly, studies in drug users found a comparable personality profile. For example, methamphetamine-dependent women revealed significantly higher levels of neuroticism and lower levels of conscientiousness, agreeableness compared with a normative sample of female respondents but differences with respect to the factor openness to experience [81]. In contrast to our findings, decreased openness in gamblers compared to controls has been reported in a study by Myrseth et al [33].…”
Section: Discussioncontrasting
confidence: 79%
“…Interestingly, studies in drug users found a comparable personality profile. For example, methamphetamine-dependent women revealed significantly higher levels of neuroticism and lower levels of conscientiousness, agreeableness compared with a normative sample of female respondents but differences with respect to the factor openness to experience [81]. In contrast to our findings, decreased openness in gamblers compared to controls has been reported in a study by Myrseth et al [33].…”
Section: Discussioncontrasting
confidence: 79%
“…This questionnaire has been repeatedly employed by different studies in Iran and other countries (Chraif & Miulescu, 2015; Hojjat et al., 2016). Moreover, the Cronbach’s alpha coefficients for the components of neuroticism, extraversion, and openness to experience, agreeableness, and conscientiousness are reported by other studies equal to .8, .58, .39, .6, and .83, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…According to Longshore that personality can affect motivation to follow treatment in drug users (Longshore, 2016). The MANOVA analysis conducted by Hojjat et shows that personality dimensions affect dependence on methamphetamine (Hojjat et al, 2016). According to Rutter and Crawford that there is a relationship between drug users who have personality disorders (low personality values) on therapeutic community participation will have a negative impact (Rutter and Crawford, 2015).…”
Section: Pembahasanmentioning
confidence: 99%